The translational genetics of ADHD and related phenotypes in model organisms. (January 2023) - Cabana-Domínguez, Judit; Antón-Galindo, Ester; Fernàndez-Castillo, Noèlia; Singgih, Euginia L.; O'Leary, Aet; Norton, William HG; Strekalova, Tatyana; Schenck, Annette; Reif, Andreas; Lesch, Klaus-Peter; Slattery, David; Cormand, Bru
Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly prevalent neurodevelopmental disorder resulting from the interaction between genetic and environmental risk factors. It is well known that ADHD co-occurs frequently with other psychiatric disorders due, in part, to shared genetics factors. Although many studies have contributed to delineate the genetic landscape of psychiatric disorders, their specific molecular underpinnings are still not fully understood. The use of animal models can help us to understand the role of specific genes and environmental stimuli-induced epigenetic modifications in the pathogenesis of ADHD and its comorbidities. The aim of this review is to provide an overview on the functional work performed in rodents, zebrafish and fruit fly and highlight the generated insights into the biology of ADHD, with a special focus on genetics and epigenetics. We also describe the behavioral tests that are available to study ADHD-relevant phenotypes and comorbid traits in these models. Furthermore, we have searched for new models to study ADHD and its comorbidities, which can be useful to test potential pharmacological treatments. Graphical Abstract: ga1 Highlights: Overview on functional work performed in rodent, zebrafish and fruit fly models of ADHD and its comorbidities. Comprehensive search for new genetically modified mouse models to study ADHD-related and comorbid traits. Review of behavioral assays available in animal models to test ADHD-related and comorbid traits. Animal models to assess environmental effects contributing to the epigenetic mechanisms of ADHD and comorbidities.